Rationales behind international students’ not selecting India as an education destination – An empirical investigation - Tarun Bhatara; Pooja Khanna (Research in Globalization)
India’s higher education sector faces significant challenges in attracting international students, evidenced by hosting less than 1 % of globally mobile students despite substantial efforts to increase this number. This study explores critical barriers preventing international students from choosing India as their destination, including financial constraints, safety concerns, and cultural integration issues. It also assesses the impact of the COVID-19 pandemic on these decisions and examines the potential of online education as an alternative. Findings reveal that inadequate financial support and safety concerns are primary deterrents, with varying impacts across educational levels and regions. Recommendations include enhancing financial aid, improving safety measures, fostering cultural integration, and leveraging online education. Addressing these issues is crucial for India to align with global education trends and improve its international appeal.